PENDAMPINGAN ORANG TUA PADA PENDIDIKAN ANAK DI MASA PANDEMI COVID-19 BERDASARKAN PROFESI ORANG TUA DI MOJOSONGO SURAKARTA - ayu, sekar; Rachmawati, Anniez (Universitas Sahid Surakarta, 2023)
The coronavirus (Covid-19) pandemic has greatly affected the way children learn. So, they need to get more support and assistance from parents, families, teachers and schools to stay focused on learning so that it continues to run well. The Covid-19 virus has spread to various countries in the world, one of which is Indonesia. Various efforts have been made to suppress the spread of the Covid-19 virus by implementing online learning. This study aims to describe the assistance provided by parents in their children's learning at home during the COVID-19 pandemic. This study uses a qualitative approach with a descriptive method to obtain information related to the involvement of parents in children's education during the COVID-19 pandemic. This data collection technique uses observation, interviews, and documentation. The results of the study show that each profession has different assistance in children's education during the Covid-19 period, and the inhibiting and supporting factors in assisting children are also different in each profession. However, all parents with various professions agree that assistance for children during the COVID-19 period is very important for children. And they keep trying to provide extra assistance to their children so that children can receive lessons very well and maximally.